EFFECT OF TAT, IT, FAT AND WCT ON ROA ON THE CONSUMER GOODS INDUSTRY SECTOR - Jessy Safitri Sitorus; Cindy Devona E Sitohang; Kartika Hardjunan; Raja Nai Zebua (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study was conducted to identify how much influence Total Assets Turnover, Inventory Turnover, Fixed Assets Turnover and Working Capital Turnover have on Return On Assets in consumer goods industry companies for the 2017-2019 period. The population of this research amounted to 54 companies